The Effect of Financial Performance, Activity Ratio, Inflation, and Exchanges Rates On Financial Distress - Risma Amalia; Bayhaqi Muhdava; Ika Amalia (Journal of Accounting and Auditing, 2026)
Purpose – This research aims to obtain empirical evidence on the influence of Financial Performance, Activity Ratio, Inflation, and Exchange Rate on Financial Distress. Design/methodology/approach – This research uses a quantitative approach. The sample consists of 92 energy sector companies listed on the Indonesia Stock Exchange between 2022-2024. The analytical technique used to test the hypothesis is logistic regression analysis using Eviews 9 software. Findings – This research of this study found that Financial Performance has a positive and statistically significant effect on Financial Distress, the Activity Ratio Variable has a negative effect on Financial Distress and is statistically insignificant on Financial Distress, the Inflation Variable has a negative effect on Financial Distress and is statistically insignificant on Financial Distress, the Exchange Rate Variable has a negative effect on Financial Distress and is statistically insignificant on Financial Distress. Research limitations/implications – This research is limited to the 2022–2024 observation period and energy sector companies listed on the Indonesia Stock Exchange (IDX), and only examines financial performance, activity ratio, inflation, and exchange rate as determinants of corporate financial distress. The practical implication of this research is that the findings may serve as a reference for management and investors in assessing and anticipating corporate financial distress risk. JEL : G33, G32, E31, F31